Konsumen Bank Islam di Indonesia: Siapa Mereka? - Panorama, Maya (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2014)
The object of this study is consumen of Islamic bank. But this study different with mostly study which is focus on factor that influence customer choosing Islamic Banking. By focus on mapping for Islamic bankâs customer in Indonesia according to their characteristic such as age, income level, level og education, and sex, this research elaborate customerâs demand basic on their characteristic. Methods use of the study by proposed a model of demand on customer. Reseach use proposed model by Dar (2008) in demand index. By this model, we found that there is 3 cateogries of Islamic Bankâs Customer with different characteristic. As a conclusion this study give recommendation how bank create their product basic on the availability of their customer based on their demand.